Find the general solution of the equation y''− 4y'+ 13y = 0.
"\\text{Given } y'' - 4y'+13y = 0 \\\\\n\\text{The auxilliary equation is of the form } m^2 -4m + 13 = 0 \\text{, using the quadratic formula we have } \\\\\nm = \\frac{4 \\pm \\sqrt{16 - 52}}{2} = \\frac{4 \\pm \\sqrt{-36}}{2} = \\frac{4 \\pm 6i}{2} = 2 \\pm 3i \\\\\n\\text{Therefore the general solution of the given differential is } \\\\\ny(x) = \\mathrm{e}^{2x} (A \\cos 3x + B \\sin 3x) \\text{ where A and B are constants.}"
Comments
Leave a comment